Exploration of PET and HDPE Plastic Waste into the Art Creating of Lampshade with Geometric Shape - Anam, Choirul; Awalizan, Mochamad Sigit (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2022)
Nowadays, waste has become a problem faced by people worldwide, especially in Indonesia. Wastes that are difficult to process, like plastics, can disturb environmental aesthetics, environmental cleanliness, and health. They have a power that is difficult to decipher, so the researcher applied several methods to them. Through an experimental process, this research designed the products of lighting elements for cafés made of plastic bottles in the types of PET and HDPE. Several phases in the testing process must be carried out to convert the wastes. First, data collection was then continued by the experiment process to produce design synthesis. In the design process, the researcher conducted waste collection, sorting, milling, washing, forming, and finishing processes. This research involved 3 sites for case studies, namely Blimbing Village TPS, Robbries Gallery as a place to search for data on waste processing processes, and Akarating Café as a theme and also as a place to look for observation data. The experimental process yielded lights used in a cafe having a hexagon shape with 2 different color accents and having different placements, such as hanging on the roof and sticking on the wall.